2016
DOI: 10.13065/jksdh.2016.16.05.701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between incivility through clinical experience and major satisfaction in dental hygiene students

Abstract: Objectives:The purpose of the study was to examine the level and relationship of incivility through clinical experience and major satisfaction in dental hygiene students. Methods: A self-reported questionnaire was completed by 357 dental hygiene students in six universities from November 1 to December 1, 2015. The questionnaire by five point Likert scale consisted of general characteristics of the subjects (6 items), incivility (20 items), and major satisfaction (6 items). Incivility was divided into three fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…2 ). Son et al [ 5 ] reported that some dental hygiene students received more discriminatory treatment than students from other schools who attended hospital clinical practice. Karatas et al [ 31 ] reported that 78.1% of nursing students in hospital clinical practice reported experiencing discrimination perpetrated by healthcare workers and fellow students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). Son et al [ 5 ] reported that some dental hygiene students received more discriminatory treatment than students from other schools who attended hospital clinical practice. Karatas et al [ 31 ] reported that 78.1% of nursing students in hospital clinical practice reported experiencing discrimination perpetrated by healthcare workers and fellow students.…”
Section: Discussionmentioning
confidence: 99%
“…The bullying, violence, and infringement of healthcare workers within medical institutions are ongoing problems and can cause serious safety and mental and physical health risks, as well as impact the organization and society as a whole [12,13]. Some healthcare students are alienated from clinical settings during their hospital clinical practice and do not receive guidelines or guidance for dealing with harassment or discrimination within their institutions [4][5][6]14]. Students may also be likely to experience human rights violations owing to a lack of experience, unfamiliarity with the clinical environment, and perceived lack of power in themselves [15].…”
Section: The Human Rights Situation In Hospital Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation